The Effect of Soy Milk Consumption on the Duration of Perineal Wound Healing in Postpartum Mothers - Usman, Hastuti; Sulistiowati, Dwi; Pont, Anna Veronica; Longulo, Olkamien Jesdika; Muliani, Muliani; Nurfatimah, Nurfatimah; Silfia, Niluh Nita; Dewie, Artika (Poltekkes Kemenkes Palu, 2024)
Perineal wounds in postpartum mothers that do not heal promptly within several days can lead to infections. Nutritional status is also considered a crucial factor in the wound-healing process. Mothers with good nutritional status tend to experience faster healing of perineal wounds, including those with protein intake from processed soy milk. This research aims to determine the impact of soy milk consumption on the duration of perineal wound healing in postpartum mothers at the Independent Midwife Practice (IMP) Sriwati Palu. The study design employed a pre-experimental design with an Intact Group Comparison approach. The sample consisted of 16 postpartum mothers with second-degree perineal wounds at the IMP Sriwati Palu, selected through quota sampling. Univariate and bivariate analyses using the Mann-Whitney U test were conducted. The research findings indicate that respondents who consumed soy milk were four times more likely to experience faster healing compared to those who did not consume soy milk. The Mann-Whitney U test yielded a ρ-value of 0.000 (<0.05), suggesting a statistically significant influence of soy milk consumption on the duration of perineal wound healing in postpartum mothers at the IMP Sriwati Palu. In conclusion, soy milk consumption has a significant impact on the duration of perineal wound healing in postpartum mothers at the IMP Sriwati Palu.